The 15-th century edition of the Pauline missal as a source for Gregorian chant history - Fryderyk Rozen (Saeculum Christianum)
There exist only few medieval codices containing musical notation for the Mass in the Pauline rite. The significant source for further research of the Pauline liturgical music is Missale Eremitarum S. Pauli printed by Johannes Amerbach about 1490. The objective of this article is to discuss the blank spaces left especially for the addition of handwritten neumes. The space for musical notation was prepared by the printer for parts of the Ordinarium Missae, in ceremonies of the Palm Sunday and Good Friday. In six remaining copies of the missal the neumes were inscribed in various ways. The study of the provenance shows that these copies were used in the monasteries in several countries.